How Feature Changes of a Dominant Ad Platform Shape Advertisers’ Human Agency - Salminen, Joni; Jansen, Bernard J.; Mustak, Mekhail (Taylor & Francis, 2022)
Businesses are increasingly delegating activities in the advertising process to dominant online advertising platforms. This delegation yields the ad platforms tremendous power, akin to the principal–agent dilemma discussed in economics. One of the major platforms is called Google Ads—this platform is the focal point of our study. Over the years, Google has made substantial changes to its platform’s features, which, in turn, govern what is possible and what is not for the advertisers. These changes impact the advertisers’ ability to act independently and make their own choices, referred to as human agency. To better understand this impact, we examined 362 industry news articles reporting changes in Google Ads from 2015 to 2020. The findings indicate that while most changes increase human agency, this effect is becoming weaker over time, driven by automation. To better understand advertisers’ attitudes towards automation, we surveyed 193 advertisers with Google Ads experience. Contrary to the popular belief that marketers are afraid of being replaced by algorithms, we found this to not be the case. Even though most advertisers indicated appreciation for maintaining their human agency, they did not perceive this agency being violated by the ad platform. However, we did observe interesting variability among respondents, reflected in three computational advertising attitude types: tinkerers, instrumentalists, and shepherds. We discuss the implications for advertisers in terms of strategizing in the face of reduced human agency and for ad platforms in terms of designing features that advertisers perceive as fair.
Keywords: advertising automation; digital marketing; Google ad platforms; human agency; online advertising; fi=Markkinointi|en=Marketing|